Barrick South America: : Sustainable Development and Community Relations - Julio E. Claudeville (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Approaches and Lessons Learned ??Address business needs?local skills training and employment ?local procurement programs ?health and safety programs ??Ensure consultants/ advisors/ contractors apply Company standards ?especially in the field/ locally ?will not be differentiated from the Company itself